Comparative Studies on the Estimated Glycemic Indices/ Loads of Fufu-Like Products from Coconut and Maize Chaffs (e-Proceedings of the Faculty of Agriculture International Conference, 2024)
Comparative studies of the estimated glycemic indices/ loads of fufu-like products made with coconut and maize chaffs were studied. Coconut chaff and maize chaff (100g each) were mixed separately with different quantities (2g, 5g and 10g) of each of the binders (psyllium husk and gelatin) and 10ml of water. The paste was stirred in a cooking pot to form dough at 1000C for 5 minutes. It was allowed to cool and packaged in transparent polyethylene bag, Hydrolysis indices, glycemic indices and glycemic loads of the fufu-like products were determined using standard methods. Hydrolysis index of the fufu-like products made from coconut chaff were found in the range of 0.41% to 0.86% while products made from maize chaff ranged from 1.08% to 6.32%. Estimated glycemic indices of the fufu-like products made from coconut chaff ranged from 39.93% to 40.18% while that of maize chaff ranged from 40.30% to 43.18%. The glycemic loads of the fufu-like product made from coconut chaff ranged from 1.78 to 4.42 (100g serving) while products made from maize chaff ranged from 6.32 to 10.34 (100g serving). The study revealed that all the fufu like products had low glycemic indices and glycemic loads except fufu-like products made with maize chaff that fell under medium range of glycemic load classifications. Fufu-like product made from coconut chaff with 10g psyllium husk yielded lowest glycemic index and glycemic load which could be used as a functional food.